IMPLEMENTASI ASEAN TOURISM SRATEGIC PLAN (ATSP) 2011-2015 DALAM MENINGKATKAN DAYA SAING PARIWISATA INDOENSIA - Raden Muhammad Randy G G, - (2018)
The tourism sector is an important sector for the integration of the ASEAN economic community. ASEAN made the ASEAN Tourism Forum (ATF) and produced the ASEAN Tourism Strategic Plan (ATSP) as a strategic direction to support the regional tourism competitiveness. This study aims to analyze the contribution provided with the establishment of ATSP in improving the competitiveness of tourism implication on economic development in ASEAN countries, especially Indonesia. The concepts and theories used are tourism, tourism competitiveness, the role of government and international cooperation. This research uses qualitative research approach with descriptive research type. This study uses primary data from PTRI documents of ASEAN, Kemenlu, and Kemenpar on ASEAN Tourism Strategic Plan (ATSP), as well as secondary data from official websites. This study uses literature study techniques and interview in data collection. From this research the results can be seen that ATSP is a step forward for ASEAN countries to meet their national interests, in the tourism sector including Indonesia. With ATSP, Indonesia has increased the number of tourist visits each year and in the index of tourism competitiveness also increased from 70th rank in 2013 to rank 42 in 2017